The mixed oligopoly of cross-border payment systems - Karlo Kauko (Bank of Finland, 2005)
This paper presents a model depicting cross-border payment systems as a mixed oligopoly.A private net settlement system that maximises profit competes with the central banks' gross settlement system that maximises welfare.It may be optimal for the central bank system to encourage increased use of the private system by charging fees that exceed the marginal cost.The central bank system is not only a competitor but also an essential service provider, because central bank money is needed for net settlement of payments in the private system.In some cases the central bank system can paradoxically induce the private system to charge lower fees by making it expensive to use central bank money for settlement purposes.
URN:NBN:fi:bof-20140807461
Keywords: L13; L44; F36; G29; 330; payment systems; network economics; mixed oligopolies